Stable Extended Imaging Area Sensing Without Mechanical Movement Based on Spatial Frequency Multiplexing - Tayebi, Behnam; Sharif, Farnaz; Karimi, Ali; Han, Jae-Ho (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
Testing process in industrial profiling depends on the characterization of three-dimensional (3-D) objects with high sensitivity in spatial and temporal domains. Ordinary 3-D measurement instruments scan the image area in the temporal domain; therefore, these techniques experience low temporal stability especially for industrial and biomedical sensing. We propose a novel scan-free extended image instrument for sensing the area of 3-D microscopic objects using an interferometric technique with fixed optical parameters, such as resolution, and without mechanical movement. The technique could accelerate the control process in industrial fault detection and images of biological samples could be obtained in a shorter time. First, a stable system for doubling the image area is introduced. Second, the principles underlying the two-dimensional sampling scheme are introduced to record the maximum image area using a dual multiplexing technique at subsampling frequency. Moreover, a standard factor is presented as a figure of merit to determine the exact image area enhancement. Finally, the feasibility of this technique was demonstrated by sensing reflective and transparent objects with image area of up to 4.3-times that of a single-hologram recording using the square scheme. Furthermore, scan-free monitoring of the photolithography process was demonstrated in real-time. The standard deviation of thickness is 0.48 nm, which demonstrates the subnanometer temporal sensitivity of this technique.
Keywords: DIFFRACTION PHASE MICROSCOPY; OFF-AXIS HOLOGRAPHY; ILLUMINATION INTERFEROMETER; DIGITAL HOLOGRAPHY; REAL-TIME; FIELD; RECONSTRUCTION; DYNAMICS; ACTUATOR; OBJECTS